Developing Empowerment Strategies and Physical Analysis of Deteriorated Urban Fabric Using an Integrated AHP and SWOT Approach (Case Study: District 12 of Tehran) - Anaraki Mohammadi, Vahid Reza; Zand Moghaddam, Mohammad Reza; Kamyabi, Saeed (Management Strategies and Engineering Sciences, 2025)
One of the challenges facing every city is the presence of deteriorated urban fabric. Deteriorated fabrics are not merely collections of buildings, streets, and alleys but are also socio-residential complexes formed by various social, economic, and cultural variables, among others. This study adopts a descriptive-analytical approach, utilizing field studies and library research methods, and employs the SWOT model and the Analytical Hierarchy Process (AHP) with the assistance of Expert Choice software. In this research, the strengths, weaknesses, opportunities, and threats of the deteriorated urban fabric in District 12 of Tehran have been analyzed. The findings from the above model analysis indicate that the most significant strengths include the preparation of a rehabilitation and renovation plan for the deteriorated fabric (final weight: 0.315), the presence of urban infrastructure such as water, electricity, and gas (final weight: 0.274), and easy access to the market and other parts of the city (final weight: 0.163). The most important weaknesses are the high unemployment rate (final weight: 0.284), low income levels (final weight: 0.195), and inadequate pathways (final weight: 0.158). Additionally, the most significant opportunities include the historical residential background dating back to the Safavid era (final weight: 0.41), proximity to city shopping centers (final weight: 0.184), and the presence of residential areas surrounding the fabric (final weight: 0.123). Meanwhile, the major threats to the area during the process of organizing, renovating, and rehabilitating include the increasing influx of migrants into the fabric (final weight: 0.349), the negative perception of others towards residing in this area (final weight: 0.216), and the lack of attention to public participation (final weight: 0.198). The final analyses in this study have led to key strategies for the improvement and renovation of the deteriorated urban fabric in the studied area.